2021
DOI: 10.1002/pc.25980
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical characteristics and hydrophobicity of alkyl ketene dimer compatibilized hybrid biopolymer composites

Abstract: In this study, the effect of alkyl ketene dimer (AKD) on the mechanical and physical properties of natural fiber (NF) and glass fiber (GF) reinforced poly(lactic acid) (PLA) composites were investigated in detail. The hybrid PLA composites were manufactured by extrusion method followed by hot press molding. AKD was used to improve the hydrophobicity of hybrid PLA composites and compatibility of NF and PLA in the polymer matrix. The tensile and flexural tests, thickness swelling, water absorption, and contact a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 48 publications
0
6
0
Order By: Relevance
“…Thus, the final properties of PMCs can be tailored by properly selecting the individual components, which usually have different physical and chemical properties. [ 4–6 ]…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, the final properties of PMCs can be tailored by properly selecting the individual components, which usually have different physical and chemical properties. [ 4–6 ]…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the final properties of PMCs can be tailored by properly selecting the individual components, which usually have different physical and chemical properties. [4][5][6] Poly (vinyl acetate) (PVAc) is a thermoplastic polymer produced by the free radical polymerization of vinyl acetate. It is a colorless polymer with intriguing properties such as non-toxicity, high flexibility, durability, ease of processing, and adhesive properties.…”
Section: Introductionmentioning
confidence: 99%
“…in terms of reduction of carbon dioxide emission, saving energy, and increase of recyclability and compostability 8 . Hence, life cycle assessment studies revealed that natural fiber composites are environmentally superior in the specific applications against glass fiber reinforced composites 9,10 . Unfortunately, lignocellulosic fibers also exhibit some disadvantages such as heat and water sensitivity and poor adhesion due to their high hydrophilic nature within the hydrophobic matrices (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…This rough structure will bring special surface properties compared with a uniform surface. [ 20 ] Zhang et al used layer structure assembly method of hydroxypropyl methylcellulose and surface coating of tannic acid on PLA film to improve its roughness. The resultant materials presented excellent ultraviolet shielding and antifogging properties.…”
Section: Introductionmentioning
confidence: 99%